2014
DOI: 10.18632/oncotarget.2774
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan treatment and senescence failure promote the emergence of more transformed and invasive cells that depend on anti-apoptotic Mcl-1

Abstract: Induction of senescence by chemotherapy was initially characterized as a suppressive response that prevents tumor cell proliferation. However, in response to treatment, it is not really known how cells can survive senescence and how irreversible this pathway is. In this study, we analyzed cell escape in response to irinotecan, a first line treatment used in colorectal cancer that induced senescence. We detected subpopulations of cells that adapted to chemotherapy and resumed proliferation. Survival led to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 47 publications
7
49
0
2
Order By: Relevance
“…Malheureusement, la sénescence induite par les thérapies anticancéreuses est peu stable. En effet, des cellules cancéreuses traitées à la doxorubicine ou à l'irinotecan, par exemple, entrent en sénescence mais, au cours du temps, certaines d'entre elles échappent à cet état [35][36][37][38].…”
Section: Resultsunclassified
“…Malheureusement, la sénescence induite par les thérapies anticancéreuses est peu stable. En effet, des cellules cancéreuses traitées à la doxorubicine ou à l'irinotecan, par exemple, entrent en sénescence mais, au cours du temps, certaines d'entre elles échappent à cet état [35][36][37][38].…”
Section: Resultsunclassified
“…We and others have shown that this suppression functions as an adaptive mechanism in response to chemotherapy-induced -senescence (CIS) (7,9). We have described that cancer cells can escape senescence and emerge as more transformed cells that resist anoikis and are more invasive (14)(15)(16)(17). In addition, we have also shown that cells having an incomplete senescence response are characterized by a reduced expression of CD47 (17).…”
Section: Introductionmentioning
confidence: 89%
“…These deleterious effects are not limited to carcinogenesis. We and others have also shown that these arrested cells and the proteins they secrete play a key role in chemotherapy resistance, allowing the generation of more aggressive cells in response to genotoxic treatments . For instance, important results indicate that Wnt activation induces the dedifferentiation of senescent cells, the reactivation of cell cycle progression, and the generation of subpopulations with higher tumor initiation potential .…”
Section: The Senescence‐associated Secretory Phenotypementioning
confidence: 95%
“…In this condition, we and others have shown that senescence relies on p21waf1 and it is not obvious that this protein is always acting as an inhibitor of cancer progression. Using different experimental models, we have shown that cancer cells enter senescence in response to chemotherapy but that persistent cells are able to escape this suppressive arrest . Senescence escape leads to the emergence of more transformed clones with enhanced potential for migration.…”
Section: Different Outcomes For Different Senescence Typesmentioning
confidence: 99%